Théologie et culture universitaire - Legrand, Hervé (Revue des sciences philosophiques et théologiques, 2008)
The way in which a theologian, ecclesiologist and ecumenist has been able to benefit from the demands of university culture. At the end of the 20th century, the relation between theology and academic procedures became less tense. The university culture has created the environment for a departure from doctrinal dogmatism and institutional fundamentalism. It has begun to enable the field of practical theology to flourish. If university culture can rightly be thought of as favourable to theology, the existence of the believer nevertheless demands a different epistemology.